Factors Affecting the Performance of Productive Zakat Management During the Covid-19 Pandemic - Intan Septiana Nazara; Anton Hindardjo; Aries Hermawan (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2022)
Factors Affecting Performance in the Management of Productive Zakat During the Covid-19 Pandemic: Case Study of BAZNAS in Labuhan Batu Regency, Islamic Banking Study Program, SEBI Islamic Economics College, 2022. This study aims to establish a good result in measuring the factors that influence the performance of productive zakat management during the Covid-19 pandemic at the BAZNAS Institute of Labuhan Batu Regency. The type of research used is quantitative research with data analysis techniques using SMART Partial Least Square (PLS) and the data collection process is carried out through questionnaires. Respondents in the study were mustahik who received the benefits of productive zakat. The results of all data analysis indicate that the effectiveness factor has no significant effect on the performance of productive zakat, while the pattern of distribution and assistance has a positive and significant effect on the performance of productive zakat.